1987
DOI: 10.1002/j.1460-2075.1987.tb02370.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence of rabbit kidney neutral endopeptidase 24.11 (enkephalinase) deduced from a complementary DNA.

Abstract: Neutral endopeptidase (EC 3.4.24.11) is a major constituent of kidney brush border membranes. It is also present in the brain where it has been shown to be involved in the inactivation of opioid peptides, methionine‐ and leucine‐enkephalins. For this reason this enzyme is often called ‘enkephalinase’. In order to characterize the primary structure of the enzyme, oligonucleotide probes were designed from partial amino acid sequences and used to isolate clones from kidney cDNA libraries. Sequencing of the cDNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
1
2

Year Published

1993
1993
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(134 citation statements)
references
References 44 publications
3
128
1
2
Order By: Relevance
“…The inhibition by EDTA and ophenanthroline has already been reported by Schiavo et al (1992b) using an in vitro test and Sanders and Habermann (1992) in an in vivo test by preincubation of the toxin with different inhibitors and subsequent injection into permeabilized bovine adrenomedullary cells. The zinc contained in the protein has been shown to be necessary for activity (Schiavo et al, 1992a) and the L chain contains the consensus sequence HEXXH found in zinc endopeptidases (Devault et al, 1987;Jongeneel et al, 1989). The histidines are implicated in zinc binding whereas the glutamate has been shown to be essential for polarization of the water molecule, a precondition for hydrolysis of the peptide bond (Matthews, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition by EDTA and ophenanthroline has already been reported by Schiavo et al (1992b) using an in vitro test and Sanders and Habermann (1992) in an in vivo test by preincubation of the toxin with different inhibitors and subsequent injection into permeabilized bovine adrenomedullary cells. The zinc contained in the protein has been shown to be necessary for activity (Schiavo et al, 1992a) and the L chain contains the consensus sequence HEXXH found in zinc endopeptidases (Devault et al, 1987;Jongeneel et al, 1989). The histidines are implicated in zinc binding whereas the glutamate has been shown to be essential for polarization of the water molecule, a precondition for hydrolysis of the peptide bond (Matthews, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The amino-acid sequence of the TeTx L chain presents the H-E-X-X-H sequence correspondi.ng to the signature of the zinc binding site of metallopeptidases (Devault et al, 1987;Matthews, 1988;Jongeneel et al, 1989;Vallee and Auld, 1990) and was recently found to contain a zinc atom (Schiavo et al, 1992b;Fraser-Wright et al, 1992). The deduced enzymic activity of TeTx L chain was formerly established by the demonstration that the toxin, but not its apoform, is able to cleave specifically rat synaptobrevin I1 at a single peptide bond (Gln76-Phe77) (Schiavo et al, 1992a).…”
mentioning
confidence: 99%
“…8B). Thus, endopeptidase 24.11, which was shown to display an N-terminal transmembrane spanning domain (Devault et al, 1987), was nearly equally solubilized by the seven detergents while alkaline phosphatase, which is covalently anchored by a glycosyl-phosphatidylinositol tail, was only released by octyl glucoside, Chaps and sodium deoxycholate (Fig. 8 B).…”
Section: Physicochemical Properties Of Kidney Endopeptidase 2416mentioning
confidence: 96%
“…Primary structures of several membrane-bound peptidases have revealed that their attachment to the membrane could occur through a NH,-terminal signal sequence (dipeptidyl peptidase IV; Ogata et al, 1989) or by a transmembrane hydrophobic sequence located at the C terminus (angiotensinconverting enzyme; Soubrier et al, 1988) or N-terminally near after a short cytoplasmic domain (endopeptidase 24.1 1 ; Devault et al, 1987;Malfroy et al, 1987). Molecular cloning of endopeptidase 24.16 should establish the type of anchor responsible for attachment of the peptidase to the membrane.…”
Section: Specificity Of Endopeptidase 2416 Towards Natural Peptidesmentioning
confidence: 99%
“…NEP has a single transmembrane domain of 22 residues, an intracellular N-terminal tail of 27 residues and a large extracellular C-terminus that contains the active site [22,23]. In contrast with the high specificity of acetylcholinesterase, NEP degrades several peptides, albeit with graded affinity.…”
Section: Degradation Of Peptide Hormones and Neurotransmittersmentioning
confidence: 99%